Sistem Informasi Analisis Volume Sampah dan Optimalisasi Rute Pengangkutan dengan Metode Neural Networks - Ira Zulfa; Eliyin Eliyin; Muhammad Yustisar; Asyam Amrullah Ar-ramdhi (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
In an age of rapid urbanization, managing waste properly is a major challenge. To deal with the increasing amount of waste, a good transportation system is needed. Therefore, the purpose of this research is to build a “Waste Volume Analysis and Transportation Route Optimization Information System using Neural Networks Method.” To precisely determine the volume of waste and design the best transportation route, this research will utilize neural networks technology. It is hoped that this system can provide innovative solutions to improve the efficiency of waste management. The research will involve collecting data on waste volume from the past and in person, analyzing it using neural networks to make precise predictions, and applying algorithms to optimize routes. This process includes data processing, modeling, and field testing of the system. This research includes results related to predicting waste volume precisely and providing visualizations that are easy to understand for use, the most efficient transportation routes that can cut operational time and costs.